The existence of the media market in Indonesia: Study of media economics at Kumparan.com and Tirto.id from an Islamic standpoint - Amallah, Nurlaillah Sari; Heryanto, Gun Gun; Sanjaya, Makroen; Marini, Marini Marini; Nisa, Ishmatun; Salas, Hagi Julio (Islamic Communication Journal, 2023)
Kumparan.com and Tirto.id now exist as online news portals that are not only written. But also through videos, images, and infographics. Like other companies, Kumparan.com and Tirto.id are profit-oriented in media economics. This research aims to reveal the existence of the media market in Indonesia related to Kumparan.com and Tirto.id reviewed from an Islamic economic perspective. This research uses an instrumental case study method that explicitly covers all aspects of the media economy at Kumparan.com and Tirto.id. This study finds that in their market role, Kumparan.com and Tirto.id make the customer the king (service market), providing full service in the form of customization to clients. As viewed from an Islamic economic perspective, universal values are the foundation for building Islamic economic theory. Such as the prophetic values (nubuwwah) that should be emulated by the Prophet Muhammad by business people, especially honesty (siddiq), responsibility (amanah), intelligence (fathanah), marketing (tabligh), and government (khalifah), then justice ('adl) must be implemented at all stages of the economy. A good business is a business that can uphold justice for its perpetrators. This study implies that media business people are prohibited from pursuing personal gain, and other parties are exploited.***Kumparan.com dan Tirto.id kini hadir sebagai sebuah portal berita online yang tidak hanya berupa tulisan, tetapi juga melalui video, gambar, dan infografik. Dalam ranah ekonomi media sama halnya dengan perusahaan lain, Kumparan.com dan Tirto.id juga berorientasi pada profit. Penelitian ini bertujuan untuk mengungkap eksistensi pasar media di Indonesia terkait Kumparan.com dan Tirto.id ditinjau dalam perspektif ekonomi Islam. Penelitian ini menggunakan metode studi kasus instrumental yang mencakup semua aspek secara eksplisit dari ekonomi media di Kumparan.com dan Tirto.id. Temuan studi ini adalah bahwa dalam peran pasar, Kumparan.com dan Tirto.id menjadikan konsumen sebagai raja (service market) yaitu memberikan servis penuh dalam bentuk kostumisasi kepada klien. Adapun ditinjau dari perspektif ekonomi Islam, terdapat nilai-nilai universal yang menjadi pondasi untuk membangun teori ekonomi Islam tersebut, seperti nilai kenabian (nubuwwah) yang patut diteladani dari Nabi Muhammad oleh para pelaku bisnis khususnya jujur (siddiq), bertanggung jawab (amanah), cerdas (fathanah), pemasaran (tablig), dan pemerintahan (khalifah), kemudian adil (‘adl) yang harus diimplementasikan pada semua tahapan ekonomi. Bisnis yang baik adalah bisnis yang dapat memegang teguh keadilan bagi para pelakunya. Implikasi dari studi nilai ini adalah bahwa pelaku bisnis media tidak dibolehkan untuk mengejar keuntungan pribadi dan adanya unsur eksploitasi kepada pihak lain.